Modeling of Steady State Operation of Two-Input DC-DC Converter for Combining of Harvested and Reserve Powers - Nakutis, Z.; Ramanauskas, R.; Kaskonas, P.; Knyva, V.; Saunoris, M.; Knyva, M. (Elektronika ir Elektrotechnika, 2013)
Modeling of the designed two input DC-DC converter for combining harvested and reserve powers is presented in the paper. Analytical model of the converter in steady state conditions was derived using differential equations averaging method. The results agreement comparing with the converter circuit simulation in LTSPICE software is shown. Analytical expression between control variables (switching duty cycles) and independent quantities (sources’ voltages and load current) is derived. A converter controller algorithm seeking to minimize the power drawn from the reserve source is suggested. DOI: http://dx.doi.org/10.5755/j01.eee.19.9.5649